THE EFFORT OF MARKETING MANAGER IN BUILDING THE IMAGE OF EVO HOTEL PEKANBARU - Lesda Oktafiani; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Image is a comprehensive assessment by consumers, guests, or customers of a hotel or company that has an impact on whether or not consumers are satisfied with the services provided by the hotel or company. The purpose of this research is to find out the efforts of Marketing Manager in building the image of Evo Hotel Pekanbaru. This research use a qualitative method with a descriptive approach by collecting data and information in the field and explaining in the form of a description without testing hypotheses or making predictions. The data analysis technique was obtained by means of observation, interviews, and documentation and then processed or analyzed to achieve the final goal. From the results of these studies, it can be concluded that the Marketing Evo Hotel Pekanbaru is very influential in building the image of the hotel. Marketing Evo Hotel Pekanbaru has made efforts to build a good image in order to create customer loyalty.  Keywords: efforts, image, marketing.